Developmental Changes in Cue Weighting for Voiceless Sibilants in Brazilian Portuguese. Issue 1 (2nd January 2019) - Penido, Fabiana A.; Rothe-Neves, Rui
ABSTRACT: An important issue regarding developmental changes in cue weighting is whether children weight the dynamic cue of vowel formant transitions relatively more than do adults, whereas adults depend more on the static cue of the fricative noise level. We investigated this issue in Brazilian Portuguese. Additionally, we inserted the segment to be classified as either [ʃ] or [s] in words versus pseudo-words. Results show that age affects the use of fricative noise level, but not of vowel transition, at least after the four years of age. These results favor the view that phonetic differences are essential for the task at hand, not only within a language but also cross-linguistically. A significant main effect of lexical status means that the experience with one's language is crucial for the distinction of phonetic segments, something so far absent from studies on developmental changes in cue weighting.